Preventing corruption in Asia: institutional design and policy capacity - Gong, Ting (Routledge contemporary Asia series, 2009)
China's war on corruption / Andrew H. Wedeman -- Rent seeking under the licensing state : the institutional sources of economic corruption in China / Tak-Wing Ngo -- Cadre recruitment and corruption : what goes wrong? / Yan Sun -- The institutionalization of party discipline inspection in China : dynamics and dilemmas / Ting Gong -- "Policing the police" : a perennial challenge for China's anti-corruption agencies / Stephen K. Ma -- Preventing corruption through performance measurement / Hon S. Chan and Jie Gao -- Japan, Korea, the Philippines, China : four syndromes of corruption / Michael Johnston -- Curbing corruption in a one-party dominant system : learning from Singapore's experience / Jon S.T. Quah -- Combating corruption in India : challenges and approaches / O.P. Dwivedi, D.S. Mishra and Meera Mishra -- Preventing corruption in Turkey : issues, instruments, and institutions / Muhittin Acar & UÄur Emek -- Ethics and corruption measures in Taiwan : the impact of democratic transformation on the national integrity system / Chilik Yu, Chun-Ming Chen, Wen-Jong Juang, & Lung-Teng Hua -- Corruption, culture and institutions : evidence from the Pacific Islands / Peter Lamour